Accounting and Fiscal Treatment of Deductions and Perishables. Measures for Reducing Food Waste - Elena STĂNCIULESCU (CECCAR Business Review)

(untitled)
In the specific agriculture and food industry activity, we often face management deficiencies caused by inherent weight losses or products that are close to expiration date. In these cases, as accounting professionals, we must know the correct application of deductions and perishables and the legal measures that must be taken to reduce food waste. We also need to know the accounting and fiscal treatment in such situations.